2022
DOI: 10.9734/ajraf/2022/v8i4182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Potting Media on the Germination and Early Growth of Newbouldia laevis. (P. Beauv.) Seem.

Abstract: The research was conducted at the screen house of the Department of Forestry and Wildlife, Faculty of Agriculture, Nnamdi Azikiwe University, Awka, Anambra state, Nigeria. The study was carried out from January to May 2021 to access the effect of different potting media on germination and early growth of Newbodia laevis. Treatments were laid out in a Complete Randomize Design (CRD) with four replications. The germination parameters measured were days to germination, germination period and germination per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
5
2
Order By: Relevance
“…This supports the research done by Marjenah et al [26] that sawdust influenced the plant height, stem diameter, and leaf production of two species of Dipterocarps seedlings. This contradicts the findings of Anozie et al [25] who recorded low collar diameter with Newbouldia laevis in treatment with sawdust.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…This supports the research done by Marjenah et al [26] that sawdust influenced the plant height, stem diameter, and leaf production of two species of Dipterocarps seedlings. This contradicts the findings of Anozie et al [25] who recorded low collar diameter with Newbouldia laevis in treatment with sawdust.…”
Section: Discussioncontrasting
confidence: 92%
“…This could be due to the lack of essential nutrients in the soil necessary for plant growth. Khan et al [24] and Anozie et al [25] found out in their studies that adding organic manure to potting media is important because it supplies essential nutrients required by seedlings for optimum growth. This however contradicts the work of Marjenah et al [26] on two species of Dipterocarps seedlings which had increase in plant height in treatment with only topsoil.…”
Section: Discussionmentioning
confidence: 99%
“…This region of southeastern Nigeria has a tropical climate marked by distinct wet and dry seasons. Average precipitation is high between 1828 mm -2002 mm per year, with a mean annual temperature of ~27°C [19], [20].…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…A potting medium is a mixture of various raw materials designed to serve as a substrate to support the roots of cultivated plants in the pots and/or containers. It is a combination of organic and inorganic materials to meet the desired chemical and physical needs of plants to enhance its growth and development [16]. A good potting mixture offers the plant a base for stability, high water capability, and good nutrient uptake, which ensures proper establishment, growth, and yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation